The role of estrogens in female lower urinary tract’s functioning and in the etiology of urinary incontinence - Adamiak, Aneta; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2003)
The experimental studies reveal that female lower urinary tract as well as micturition centres in the brain cortex, pontine or forebrain are the target tissues for estrogens. These hormones have the influence on biomechanical properties of female pelvic floor structures so they play an important role in the urinary continence mechanisms. The epidemiological studies reveal that menopause with subsequent hormonal defficiency has been implicated in the etiology of a number of urogenital complaints. In this period the increased ocurrence of stress urinary incontinence, overactive bladder and recurrent tract urinary infection is observed. The aim of this paper is to present the actual knowledge about the role of estrogens in the female lower urinary tractfunctioning and the etiology of urinary incontinece.